Dinamika Perkembangan Kewenangan Mahkamah Konstitusi - Umar, Kusnadi; Sofyan, Sofyan (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2023)
The Constitutional Court as the guardian of the constitution has a central role in a constitutional-democratic state. This study aims to reveal the extent of the development of the authority of the Constitutional Court in the constitutional system using a normative juridical approach. The results showed that the Constitutional Court experienced a